The Implementation of the Tabayun Concept in Islamic Religious Education as an Effort to Foster Students’ Moral Character in the Digital Era - Nabil Tito Prasetyo; Hikma Apriani; Agus Pahrudin; Achi Rinaldi; Ali Murtado (at-Tarbiyah al-Mustamirrah: Jurnal Pendidikan Islam, 2026)
The rapid development of digital technology has brought various challenges to students' moral development, particularly regarding social media use and the spread of unverified information. Islamic Religious Education plays a strategic role in instilling moral values that are relevant to digital life, one of which is the concept of tabayun (verification and clarification of information). This study aims to describe the implementation of the tabayun concept in Islamic Religious Education as an effort to foster students' moral character in the digital era. The study employed a qualitative approach, with data collected through observations, interviews, and documentation conducted within the school environment. The findings reveal that the implementation of tabayun was carried out through contextual learning based on social media cases, the habituation of information verification practices, the strengthening of digital literacy, and teachers' role modeling in the responsible use of digital media. These practices serve as an effort to foster students' moral character, as reflected in the development of critical thinking, greater caution in receiving information, and more responsible behavior in digital interactions. Keywords: Tabayun, Islamic Religious Education, Students' Moral Character, Digital Era, Digital Literacy